SEBARAN POTENSI KONFLIK BUAYA MUARA DI KECAMATAN TANJUNG MUTIARA, KABUPATEN AGAM, SUMATERA BARAT - Mubarok, Zaki; ., Ahyuni (JURNAL BUANA, 2024)
Human conflicts with crocodiles have become a problem that affects crocodile conservation. Scientific publications on crocodile attack cases in Indonesia are still scarce and need validation, thus mitigation efforts for conflicts are not yet optimal. Tanjung Mutiara Subdistrict is an area with the highest incidence of human-crocodile conflicts in West Sumatra, as it has a natural crocodile habitat directly bordering densely populated settlements and community plantations. This research aims to map the distribution of estuarine crocodiles and the potential for conflicts in surrounding settlements. Data processing was conducted using Maxent software, and environmental variables included distance from the river, distance from the coast, distance from plantations, land cover (shrubland), elevation, and temperature. The Maxent software prediction results indicate that the distance from the river is the most influential variable, with an AUC (Area Under Curve) value of 0.863. The output values' range, approaching 1, signifies better predictions. Settlements with activities within one kilometer from the river and coast have the highest potential for human-crocodile conflicts.